Komunikasi Simbolik Dalam Proses Ritual Pasa’a Ate’ Luma Latu Karas Negeri Hitu Lama - Rumra, Fatmawati (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2022)
The results showed that the symbolic communication contained in the ritual process of Pasa'a Ate Luma Latu Karas could be seen through 3 core stages such as before the ritual process, in the ongoing ritual process, and the process after the Pasa'a Ate Luma Latu Karas ritual occurs. The next stage is interpreting the ritual process of Pasa'a Ate Luma Latu Karas by describing the meaning through the symbols contained in the ritual process. After that, the interpretation of the ritual process was continued by analyzing each ritual procession using the theoretical aspects of George Herbert Mead, which consisted of action, gestures, significant symbols, mind, self, and society. Through the results of this analysis, it can be seen that the meaning of the symbols contained in the ritual process of Pasa'a Ate Luma Latu Karas forms the interaction among the Raja, adat leaders, and the community.